Combined effect of pulsed electromagnetic field and sound wave on In vitro and In vivo neural differentiation of human mesenchymal stem cells. (18th November 2016) - Choi, Yun‐Kyong; Urnukhsaikhan, Enerelt; Yoon, Hee‐Hoon; Seo, Young‐Kwon; Cho, Hyunjin; Jeong, Jong‐Seob; Kim, Soo‐Chan; Park, Jung‐Keug
Abstract : Biophysical wave stimulus has been used as an effective tool to promote cellular maturation and differentiation in the construction of engineered tissue. Pulsed electromagnetic fields (PEMFs) and sound waves have been selected as effective stimuli that can promote neural differentiation. The aim of this study was to investigate the synergistic effect of PEMFs and sound waves on the neural differentiation potential in vitro and in vivo using human bone marrow mesenchymal stem cells (hBM–MSCs). In vitro, neural‐related genes in hBM–MSCs were accelerated by the combined exposure to both waves more than by individual exposure to PEMFs or sound waves. The combined wave also up‐regulated the expression of neural and synaptic‐related proteins in a three‐dimensional (3‐D) culture system through the phosphorylation of extracellular signal‐related kinase. In a mouse model of photochemically induced ischemia, exposure to the combined wave reduced the infarction volume and improved post‐injury behavioral activity. These results indicate that a combined stimulus of biophysical waves, PEMFs and sound can enhance and possibly affect the differentiation of MSCs into neural cells. Our study is meaningful for highlighting the potential of combined wave for neurogenic effects and providing new therapeutic approaches for neural cell therapy. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 33:201–211, 2017